2012
DOI: 10.1038/bjc.2012.323
|View full text |Cite
|
Sign up to set email alerts
|

Expression of oestrogen receptor β and prognosis of colorectal cancer

Abstract: Background:Previous studies suggest that sex steroids influence colorectal cancer (CRC) carcinogenesis. The oestrogen receptor β (ERβ) is the predominantly expressed ER in the colon and loss of ERβ in CRC has been associated with advanced cancer stages.Methods:Information on vital status by the end of 2009 was obtained for 1262 CRC patients recruited between 2003 and 2007. The ERβ expression was immunohistochemically measured and associations of ERβ scores with overall survival (OS), disease-specific survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 37 publications
8
86
3
Order By: Relevance
“…Clinical and experimental models of colonic carcinogenesis have suggested that the protein expression of ERb decreases as the tissues progress from a normal colonic epithelial to a malignant state (Konstantinopoulos et al 2003, Castiglione et al 2008, Di Leo et al 2008, Mostafaie et al 2009). In fact, humans with colon tumors not expressing ERb are likely to be in more advanced stages of cancer and have a higher risk for death compared with those with tumors in which ERb is present (Rudolph et al 2012). ERb expression levels in this study suggest that a similar trend occurs during the formation of inflammation-associated colon tumors.…”
Section: Discussionsupporting
confidence: 57%
“…Clinical and experimental models of colonic carcinogenesis have suggested that the protein expression of ERb decreases as the tissues progress from a normal colonic epithelial to a malignant state (Konstantinopoulos et al 2003, Castiglione et al 2008, Di Leo et al 2008, Mostafaie et al 2009). In fact, humans with colon tumors not expressing ERb are likely to be in more advanced stages of cancer and have a higher risk for death compared with those with tumors in which ERb is present (Rudolph et al 2012). ERb expression levels in this study suggest that a similar trend occurs during the formation of inflammation-associated colon tumors.…”
Section: Discussionsupporting
confidence: 57%
“…In agreement with this finding ERb has been shown to stimulate antiinflammatory networks in colon cancer cell lines (Edvardsson et al 2011). Expression of ERb in colon cancer is correlated to prognosis where a decreased expression is found in higher grade and larger tumors (Konstantinopoulos et al 2003, Rudolph et al 2012, and the level is inversely correlated with more advanced Dukes' staging (Jassam et al 2005). A role of ERa in colon cancer has not been found so far.…”
Section: Colonsupporting
confidence: 64%
“…Whether ESR2 expression in colorectal cancer is associated with microsatellite status remains to be clarified, as Wong and colleagues found that ESR2 isoform 1 expression was decreased in microsatellite stable colorectal cancer compared with microsatellite-unstable colorectal cancer, but no differences in expression were observed for isoform 2 and 5 (22). We also did not observe differences in ESR2 expression according to microsatellite status in the DACHS study population (10). One study reported significantly different associations between current use of menopausal hormone therapy and colorectal cancer risk according to CDKN1A expression (19).…”
Section: Discussionmentioning
confidence: 49%
“…A potential mediator of estrogen effects is the estrogen receptor-b (ESR2), which is the primarily expressed estrogen receptor in the large intestine (1). Loss of ESR2 expression in tumor tissue of patients with colorectal cancer has been associated with poorer differentiation of tumors and more advanced cancer stages (7)(8)(9)(10). However, it has also been postulated that endogenous and exogenous sex hormones may have differential effects on the development of colorectal cancer (6), as high levels of endogenous estrogens have been found to be associated with an increased risk for colorectal cancer (11,12).…”
Section: Introductionmentioning
confidence: 99%